Policies and Strategies for Green Tourism Development of the Jeneberang River Area in Makassar City - Faisal Faisal; Rahmanita; Nurbaeti (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2024)
The Jeneberang River has enormous potential to be developed as a green tourism destination in the city of Makassar. The potential it has consists of the natural base potential as one of the largest rivers in South Sulawesi province in the form of water and all the biota that form a single river ecosystem, panoramic views of the area located at the estuary, which is directly connected to the sea in the Makassar Strait, richness of land vegetation along the banks, rivers in river border areas, and beaches. This research is descriptive research with a normative approach to determine the objectives, implementation, and impact of tourism development policies on the existence of the Jeneberang River as a green tourism destination in the city of Makassar. The research respondents were 17 people from representatives of each element of Makassar city tourism stakeholders. Data was collected through in-depth interviews and searching for documents relevant to the policy for developing the Jeneberang River as a green tourism destination. The research results found that the development of the Jeneberang river has been stipulated in several regional policies in the form of regional regulations, namely Makassar City Regional Regulation Number 4 of 2015 concerning Makassar City Regional Spatial Plan for 2015-2034 and Makassar City Regional Regulation Number 5 of 2023 concerning Development Master Plan Makassar City Regional Tourism 2023-2025. Operationally, this policy has not been supported by technocratic planning in the form of the Jeneberang River Development Masterplan as a Green Tourism Destination